2014
DOI: 10.1517/13543784.2014.922951
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase activators in diabetic ulcers: from animal studies to Phase II drugs under investigation

Abstract: Animal studies have demonstrated that AMPK activators are a potential treatment for diabetic ulcers. AMPK activators alleviate tissue inflammation and promote re-epithelialization in diabetic wounds. However, due to the complicated pathological mechanism of diabetic foot ulcers, AMPK activators should be combined with other approaches. The new strategies for combination therapy with AMPK activator may provide a therapeutic advantage for patients with diabetic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…It should be noted that the improvement that resulted from MET might also be linked to non-glucose-lowering mechanisms, most of which are known to be associated with AMPK activation (48,49). AMPK, as a major cellular energy sensor, plays a positive role in diabetes-associated complications (50,51). Recently, AMPK activation has been shown to reduce HG-induced ␣-SMA expression by inhibiting nuclear translocation of Smad4 (60).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the improvement that resulted from MET might also be linked to non-glucose-lowering mechanisms, most of which are known to be associated with AMPK activation (48,49). AMPK, as a major cellular energy sensor, plays a positive role in diabetes-associated complications (50,51). Recently, AMPK activation has been shown to reduce HG-induced ␣-SMA expression by inhibiting nuclear translocation of Smad4 (60).…”
Section: Discussionmentioning
confidence: 99%
“…It exerts its antihyperglycemic effect at several levels including inhibition of hepatic glucose production, reduction of intestinal glucose absorption, improvement of glucose uptake, and utilization by peripheral tissues [72]. Emerging evidence indicates novel pleiotropic effects of metformin that include potential renal and cardiovascular protection, antioxidant, antifibrotic, and antiproliferative properties [73] and the ability to increase number and function of endothelial precursor cells [74,75]. Metformin's mechanism of action is linked to inhibition of the complex 1 of mitochondrial electron transport chain and subsequent reduced ATP production and increased AMP:ATP ratio with activation of 5 -AMP-activated protein kinase (AMPK).…”
Section: Metforminmentioning
confidence: 99%
“…a higher AMP/ATP ratio), AMPK balances energy consumption by inhibiting energy/ATP-consuming pathways and activating the compensatory energy/ATPproducing processes. In addition to the traditional role of AMPK in energy metabolism, several studies have indicated a pivotal role of AMPK in immune regulation (Sag et al, 2008;Viollet et al, 2010;Lin et al, 2014). Using AMPK activators (5-aminoimidazole-4-carboxamide-1-β-Dribofuranoside, AICAR) and inhibitors (Compound C) (Corton et al, 1995;Zhou et al, 2001), there is now ample evidence that AMPK1α, through its signalling network, suppress inflammation (Salt and Palmer, 2012;Palomer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%